If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + (X + 2) + 2 = 14 Reorder the terms: X + (2 + X) + 2 = 14 Remove parenthesis around (2 + X) X + 2 + X + 2 = 14 Reorder the terms: 2 + 2 + X + X = 14 Combine like terms: 2 + 2 = 4 4 + X + X = 14 Combine like terms: X + X = 2X 4 + 2X = 14 Solving 4 + 2X = 14 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 2X = 14 + -4 Combine like terms: 4 + -4 = 0 0 + 2X = 14 + -4 2X = 14 + -4 Combine like terms: 14 + -4 = 10 2X = 10 Divide each side by '2'. X = 5 Simplifying X = 5
| (b)5x-3=7 | | 9.39=w+2 | | 7x^2+9x=-1 | | 4w+6y+7x+8x-14y+3w= | | 1100+800+5x=600+500+9x | | 8/3q=2/2q+1 | | 7x^2+9=-1 | | 3x-5-13=-2x+2-13 | | 8n+7=37 | | 2w+5w-15y+5w+10x+7y= | | 4(8x-9)= | | 6x+40=15x-42 | | 2x^2-7=3x+4 | | -2y*2=0 | | (a)5w+3=4w+9 | | k+hj=6 | | 3-6x=11x-8x | | -2y*-y=0 | | 6a^2-30a+24= | | 2.7x+2.8=19 | | -17=3+5 | | 9x-12+2x=11x+6 | | d-2.94=1.36 | | 2(3x+4)-3=6x+5 | | -5+9=21 | | 3m-10=24m-5 | | x/18+x/3 | | 8(y+6)+y=4(y+5)+2 | | 1/31/2x/3 | | -4(3x-4)+1=-12x+17 | | 5x+4=12+5x | | 2x-3+4x-8=13 |